Economic governance and security perspective in West Africa: The role of ECOWAS - Terwase, Isaac Terungwa; Abdul Talib, Asmat Nizam; Zengeni, Knocks Tapiwa (2014)
The West African States are known for endowed natural and human resources that ought to have an enlargement in the area of economic growth and development which will yield results to the countries in West Africa through economic cooperation among states within the region. It is therefore, the goals and objective of the Economic Community of West African States (ECOWAS) is to promote regional integration and co-operation for the purpose ensuring economic growth and development through economic and monetary union among the states in the sub-region.The endowed resources in West African states are mostly untapped due to challenges that face the region such as lack of technological know-how, bad governance, political instability, lack of adequate diversification, infrastructure problem, lack of political will and the inability to involve the private sector, partnership with other countries outside Africa.The objective of this research is therefore, to create an environment where peace and security is sustainable for West African states to engineer economic governance through regional integration and economic co-operation among the countries in West Africa, partnership with the private sector, other African countries, the international community, and as well as countries from Asia, America, Europe and Australia which will lead to economic growth and development in West African States.The methodology used in this research is review of previous literatures and the use of content analysis which will also provide useful information on the available resources in the region.The findings from this study thus, the security of the West African states is very essential for the purpose of economic governance to be effective in the region where the states can engage in economic integration and co-operation. Through the role of ECOWAS in engineering economic growth and development therefore, envisioned the role of partnership with other countries outside Africa to solve the faced challenges in the region.